Thinking through Community Spirit: Zainichi Koreans in Post-Korean Wave Japanese Communities - Demelius Yoko (Taylor & Francis, 2022)
This article explores the notion of ‘community spirit’ as it occurs in the discourse of community development (machizukuri) in the context of a society characterised by multicultural coexistence (tabunka kyōsei). It does so by examining multigenerational Korean residents’ integration in post-Korean Wave Japan. Despite the recognised deficiencies in Japan’s attempt to accommodate ethnic diversity in line with the government’s vision of multicultural coexistence, some long-term Korean and Japanese residents have begun to foster a shared sense of community as Japanese consumers of mainstream culture have familiarised themselves with Korean culture in recent years. Inspired by the existing gap between community spirit embodied among residents and the Japanese government’s sustained rhetoric aimed at maintaining the existing social order by juxtaposing Japanese and non-Japanese residents, this article aims to identify the keys to fostering an effective vision of an inclusive society in Japan. I argue that informal networks, personal engagement, and active participation would complement the current top-down policy that is implemented to negotiate Japan’s increasing diversity. Based on data gathered during ethnographic work that included participation in community initiatives and council discussions in western Japan’s Hanshin area, I shed light on the competing forces of inclusion and exclusion in contemporary Japanese society.